Optimizing Detection of Major Depression Among Patients with Coronary Artery Disease Using the Patient Health Questionnaire: Data from the Heart and Soul Study - Thombs, Brett D. (Springer-Verlag, 2008)
BACKGROUND: Clinical guidelines recommend depression screening in patients with coronary artery disease (CAD), but how to accomplish this is unclear. OBJECTIVE: We evaluated the test characteristics of the two-item Patient Health Questionnaire (PHQ-2), the nine-item Patient Health Questionnaire (PHQ-9), and a two-step screening approach (PHQ-2 then PHQ-9 if positive on PHQ-2), compared with the Computerized Diagnostic Interview Schedule (C-DIS) for major depression. We also evaluated a “PHQ diagnosis” of depression, requiring five of nine symptoms “more than half the days,” compared with the C-DIS. DESIGN: Cross-sectional study of 1,024 outpatients with CAD. MAIN RESULTS: Two hundred twenty-four patients (22%) had current major depression. Optimal cutpoints were ≥2 for the PHQ-2 (82% sensitive, 79% specific) and ≥6 for the PHQ-9 (83% sensitive, 76% specific). The two-step screening approach was less sensitive (75%), but more specific (84%), than the PHQ-2 or PHQ-9 alone. The “PHQ diagnosis” had low sensitivity (28%), but high specificity (96%). CONCLUSIONS: Cutpoints of ≥2 on the PHQ-2 and ≥6 on the PHQ-9 had similar test characteristics. A two-step approach using the PHQ-2 followed by the PHQ-9 was no better than either instrument alone. A “PHQ diagnosis” of depression had high specificity, but poor sensitivity.